Whiteheadian Ethics : Abstracts and Papers from the Ethics Section of the Philosophy Group at the 6th International Whitehead Conference at the University of Salzburg, July 2006. - Theodore Walker and Mihály Tóth (Cambridge Scholars Publishing, 2008)
For deliberations on the ethical and meta-ethical implications of Alfred North Whiteheadâs process philosophy, here are abstracts and papers from the Ethics Section of the 6th International Whitehead Conference held at the University of Salzburg in Salz.